Bioactive flavonoids metabolites in citrus species: their potential health benefits and medical potentials - Xu, Yuqian; He, Pan; He, Beihui; Chen, Zheng (Frontiers in Pharmacology, 2025)
Citrus flavonoids are naturally occurring phytochemicals widely present in the peels and pulps of citrus fruits. They exhibit a wide range of biological activities, including antioxidant, anti-inflammatory, hypoglycemic, lipid-lowering, antimicrobial, and gut-protective effects. These metabolites show great potential in improving metabolic syndromes such as diabetes, non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases. Additionally, citrus flavonoids have demonstrated significant effects in inhibiting pancreatic lipase activity, regulating lipid metabolism, and enhancing intestinal barrier function. Advances in extraction and purification techniques have further promoted their applications in the fields of food, medicine, and functional materials. This review systematically summarizes the types, bioactivities, and mechanisms of action of citrus flavonoids, providing scientific evidence for their research and development.